Enforcement of Foreign Arbitration Awards - Elhaj, Babiker Mustafa Mohamed (2013)
The dissertation examines in depth and focuses on enforcement of the foreign arbitration awards based on the national laws and treaty obligation as applied in the UAE. The im-portance of this study is derived from the fact that enforcing arbitral award is the ultimate aim and outcome of the entire arbitration process. So it is extremely significant for inter-national businesses and it will lead to stability and progress since the arbitral award is not useful if it’s not enforced smoothly and expeditiously. It’s well-known that arbitration became evident recently due to the huge growth and expansion in the international trade and investments between different countries. Accordingly, the arbitration has emerged as the preferred mechanism for resolving the disputes due to the huge advantages thereof. Arbitration is the quicker and most simple way for resolving various international, and commercial, civil and economic disputes in the Arab world and particularly in the UAE as well as other countries in the world. Therefore, arbitration will be useless and a waste of effort, time and money unless it is enforced as per the provisions of the law and the international treaty obligations. This study defines and elaborates the foreign arbitration, foreign arbitral awards and en-forcement, and also discusses the methods and procedures of enforcing arbitral awards and clarifies the issues that may result in refusal of enforcement, setting aside and nullifying the arbitral awards by the national courts. Further, the study enlightens the procedures and conditions concerning enforcement processes in light of the New York Convention of 1958 and some international, regional and bilateral conventions as well as the legal procedures necessary for enforcing the foreign arbitral awards in the UAE, in addition to the formalities and mechanisms necessary for enforcing the foreign arbitral awards. Moreover, this research analyses and sheds light on the international, regional and bilateral conventions and agreements ratified by the UAE that will clarify the necessary mecha-nisms to facilitate enforcing foreign arbitral awards under the provisions of national laws as well as the state's treaty obligations, such as the New York Convention, GCC Treaty, Riyadh Convention of Arab League, and bilateral agreements with some states such as France, India and some Arab countries. Further, the study deals with some legal issues related to this essential topic. Looking at other laws in the GCC states in addition to some Arab and foreign countries is also possible. The study contains some interviews and communications with judges, arbitrators, lawyers and legal experts with regards to enforcing foreign arbitral awards, along with an analysis of some judgments issued by various courts regarding the subject matter. Finally, the study provides conclusion and recommendations.